Successful Plant Regeneration from Callus Culture Through Organogenesis in Premna Serratifolia L.-an important medicinal tree (Open Access Journal of Medicinal and Aromatic Plants, 2011)
A successful protocol is described for rapid and large scale propagation of woody aromatic medicinal tree, Premna serratifolia L. by in vitro culture of nodal segments from mature plants. Murashige and Skoog (MS) medium supplemented with various concentrations of 6-benzylaminopurine (BAP), kinetin and indole 3-acetic acid were examined for their effects on multiplication. The most promising treatment was 3.0 mg/l BAP and 0.5 mg/l kinetin which increased shoot number and explants weight within four weeks. High frequency callus initiation and synergistic effects on callus growth were achieved on MS medium supplemented with 5.0 mg/l indole acetic acid within two weeks of culture. Rooting was achieved after four weeks of subculture with 67.8% of the node cuttings on half strength MS medium supplemented with 1.0 mg/l naphthalene acetic acid. Regenerated plants were successfully acclimated on sterilized sand for 28 days but for further growth of plant, sand: soil mixture (1:1) was found as the best substrate. The survival rate of plantlets under ex vitro conditions was 89% after three months. The optimized micropropagation and callus culture protocols offer the possibility of using organ culture technique for vegetative propagation, cryopreservation and secondary metabolism studies.